AI-based cyber patrol system for media sentiment analysis on online news regarding the Indonesian Air Force - Muhammad Iqbal Setyawan; Adam Mardamsyah; Anindito Anindito; Dwi Cahyo Budiman (Institute of Computer Science (IOCS), 2026)
This study presents the development of an adaptive cyber patrol system designed to assist the Indonesian Air Force in monitoring the rapidly changing dynamics of public information. The system aims to detect issues that may influence strategic perception and operational readiness by automatically tracking online news sources across Indonesia. The integrated framework automates the collection, Analysis, and reporting process ranging from identifying viral phrases and performing sentiment Analysis to generating tactical reports for Download. Artificial intelligence techniques are employed to expand keyword coverage, ensure the timeliness of information, and assess the relevance and coherence of collected content. Evaluation results indicate that the system operates reliably and produces well-structured outputs. Overall, this research offers a modular integration of AI, information Analysis, and automated reporting that can be further developed toward predictive and multi-tenant analytics in the future.